Motor Franchise Claim System (MFCS) / Doraisamy Ramasamy - Doraisamy , Ramasamy (2004)
The project that I undertake is called Motor Franchise Claim System (MFCS). The objective and scope of the project is widely explained in the chapter 1. This system is mainly designed for Malaysia Motor Franchise Holders to operate and monitor motor claims involving their workshops spread through nationwide. The MFCS is an online web based system. Hence, reasonable interactive features are expected to be used to make the system dynamic and attractive. The wide range of system requirements which includes the authoring tools, programming languages, scripting languages, web servers are widely discussed in Chapter 2. The rationale to design this system is that, at the present moments, Motor Franchise Holders does not have own a motor claims system. They are still practicing the manual file system which most organization looking for paperless environment. Furthermore, third parties that are benefiting in the expense on the Insurance Companies currently provide the existing claim system.